The Deixis in Ali Ebn Gahmm,s Blame to Abi hamaziat Tammam - al-Shammari, Awad bin Baiq (Journal of Humanities & Social Sciences, 2021)
This study aimed to identify the importance of Deixis and their various connotations, to reveal Deixis in the poem attab- the subject of research, and to shed light on the most prominent type of Deixis contained in the poem - the subject of research The study relied on the deliberative approach, as the consultants fell under deliberative framework, with the benefits of description, analysis and statistics mechanisms, as needed. The study has reached several results, the most important of which are: the richness of Hamzia Ali ibn Jahm in Abu Tammam’s reproach of Deixis, and the link between cosmic and grammatical time in the verses of the poem, and the roses of temporal compositions unlike its origin, to indicate certain contextual implications. The study recommends the importance of expanding the study of Deixis and applying them to prose texts among Arabs.